Digital surveillance and athlete privacy in elite sport: a prisma 2020-based systematic literature review - Anisa Sholiha Mia; Ifdil Ifdil; Rudyanto Rudyanto (Lentera Negeri, 2026)
Rapid adoption of wearable sensors, biometric monitoring and AI has dramatically changed the athlete monitoring scene in high-level sports, with performance maximisation and injury prevention significantly improved alongside emergence of privacy, autonomy and data governance-related issues. This systematic literature review combines the latest research on the digital surveillance aspect and athlete privacy in top sports and high-performance sport while particularly examining the ethical, legal and governance effects of data-driven monitoring. The review method strictly followed PRISMA 2020 guidelines. Initially 748 research records found on a Scopus database with a structured search and after the screening process, 10 peer-reviewed publications satisfied all inclusion criteria. The articles selected for the review covered the topics of monitoring via surveillance, privacy, consent, autonomy or governance issues. Thematic synthesis uncovered three key areas: First, through extensive data collection, continuous biometric and location monitoring has enabled the organization to exercise a great amount of control over the athletes. Second, due to the employment dependence and high-level pressure of athlete competition, the athletes' free will is highly limited and even the athletes' privacy in terms of information they can provide or know about their data is very limited. Third and finally, privacy-preserving technologies, data co-ownership, data sovereignty frameworks and similar governance tools are still in rudimentary states and not able to follow the speed of development of the technology. Besides being the review paper on technology-aided monitoring in sports, this paper relates the changes within sports to the general theory around how our lives become data-centric and our activities are watched. Also, it underscores the importance of procedures for obtaining valid consent, limitation of data collection and use to specific purposes and having external auditors or authorities to carry out independent checkups or oversight. Research is urged to focus on producing athlete-centred evidence, examining different governing models, comparing regulations in different countries and helping to establish the ethical digital monitoring for elite sports.